PROMOTING STUDENTS’ EXPLICIT INFORMATION SKILL IN READING COMPREHENSION THROUGH GRAPHIC ORGANIZERS - Syaifudin Latif Darmawan (Premise: Journal of English Education and Applied Linguistics, 2013)
This research is carried out to (1) identify whether graphic organizers can improve students’ reading comprehension; and (2) to describe the classroom situation when graphic organizers are employed in instructional process of reading comprehension. The research is adminisitered in two cycles 2014 in the second grade of SMP Muhamadiyah Sekampung, Lampung Timur. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. Qualitative data are collected through interview, observation, questionnaire, and research diary. Quantitative data are collected through test. To analyze qualitative data, the researcher used constant comparative method. It consists of four steps: (1) comparing incidents applicable to each category; (2) Integrating categories and their properties; (3) delimiting the theory; (4) Writing the theory. Meanwhile, to analyze quantitative data, the researcher employed descriptive statistic.    The result of the research shows that using graphic organizers can improve students’ reading comprehension and classroom situation. The improvement on students’ reading comprehension is students are able to find explicit information in a text. The improvement of the classroom situation; (a) students come on time in the class (b) students are more motivated to join the class (c) Students pay more attention in the instructional process. In addition, the improvement also happens to the scores. The mean score increases from 57.56 in the pre-test, 63.34 in the formative test of cycle 1, and 69.56 in the post test of cycle 2